Some Reasoning Methods and Analytical Models in the Teaching process - Crnjac Milić Dominika (Array, 2009)
This work discusses reasoning methods in teaching process: total induction, partial induction, deduction, analogy and intuition.It gives examples of reaching conclusion by induction.It presents deduction as reliable reasoning method and points that inductive and indirect arguments are part of deductive n+method.Analogy and intuition are also presented as valid method for teaching process.This research was part of main Scientific reasrch named Analytical Model for Monitoring of New Education Tehnologies for Longlife Learning conducted by Ministry of Science, Education and Sports of the Republic of Croatia.